FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN INFEKSI SALURAN PERNAPASAN AKUT (ISPA) PADA BAYI DI WILAYAH KERJA PUSKESMAS KAMPUNG BARU KECAMATAN MEDAN MAIMUN TAHUN 2017 - Leli Fatimah Nasution; Hiswani .; Sri Novita Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2018)
ABSTRACT Acute Respiratory Infection (ARI) is the major cause of morbidity and mortality of infectious diseases in the world, it is one of the main cause of consultation or inpatient in the health service, especially in the child care section. PMR of ARI in toddlers in the world were 26,7%. The prevalence of ARI in Indonesia at 2013 was 25,0%. The aim of this research is to determine factors related with ARI in infants in the Puskesmas Kampung Baru Medan Maimun districk at 2017. This research was an analytic using cross sectional design. The population of this research were all infant that is in the working area Health Center of Kampung Baru and the sampling tehnique is purpossive sampling for 103 person. Data were analyzed by chi square test with 95% CI. The result of research indicates that prevalence rate of ARI is 59,2%, the highest frequency distribution on the 11 month old 16,5%, female 51,5%, good nutrition status 79,6%, exclusive breastfeeding status 53,4%, not yet received DPT/Hib and measles, for immunization status 63,1%. For the characteristics of the mother, the highest proportion were senior high school 68,0% and housewife job 78,6%. For the characteristics of the environment, the highest proportion were occupation density 55,3%, used burnt mosquito coils 93,2%, used lpj 82,5%, and existence of smoker 81,6%. The result of statistic analysis indicates there is a significant relationship of age (p=0,022), nutrition status (p=0,034), exclusive breastfeeding status (p=0,025), occupation density (p=0,034), and existence of smoker (p=0,028) with incident of ARI. It is suggested to the mothers for giving exclusive breastfeeding, that was a human right of the infants, for giving of good nutrition for the growth and development of infants, and then for the family members to not smoke when at the home. Keywords : ARI, Infants, Puskesmas Kampung Baru